Reseña de Couper-Kuhlen, E. y B. Kortmann (eds.) (2000), Cause, Condition, Concession, Contrast. Cognitive and Discourse, Perspectives. - Laura Miñones (Pragmalingüística)
Se trata de una reseña de Couper-Kuhlen, E. y B. Kortmann (eds.) (2000), Cause, Condition, Concession, Contrast, Cognitive and Discourse, Perspectives.